The Sumo proteome of proliferating and neuronal-differentiating cells reveals Utf1 among key Sumo targets involved in neurogenesis - Correa-Vázquez, Juan Francisco; Juárez-Vicente, Francisco; García-Gutiérrez, Pablo; Barysch, Sina-Victoria; Melchior, Frauke; García-Domínguez, Mario (Cell death & disease, 2021)
Post-translational modification by covalent attachment of the Small ubiquitin-like modifier (Sumo) polypeptide regulates a multitude of processes in vertebrates. Despite demonstrated roles of Sumo in the development and function of the nervous system, the identification of key factors displaying a sumoylation-dependent activity during neurogenesis remains elusive. Through a SILAC (stable isotope labeling by/with amino acids in cell culture)-based proteomic approach, we have identified the Sumo proteome of the model cell line P19 under proliferation and neuronal differentiation conditions. More than 300 proteins were identified as putative Sumo targets differentially associated with one or the other condition. A group of proteins of interest were validated and investigated in functional studies. Among these, Utf1 was revealed as a new Sumo target. Gain-of-function experiments demonstrated marked differences between the effects on neurogenesis of overexpressing wild-type and sumoylation mutant versions of the selected proteins. While sumoylation of Prox1, Sall4a, Trim24, and Utf1 was associated with a positive effect on neurogenesis in P19 cells, sumoylation of Kctd15 was associated with a negative effect. Prox1, Sall4a, and Kctd15 were further analyzed in the vertebrate neural tube of living embryos, with similar results. Finally, a detailed analysis of Utf1 showed the sumoylation dependence of Utf1 function in controlling the expression of bivalent genes. Interestingly, this effect seems to rely on two mechanisms: sumoylation modulates binding of Utf1 to the chromatin and mediates recruitment of the messenger RNA-decapping enzyme Dcp1a through a conserved SIM (Sumo-interacting motif). Altogether, our results indicate that the combined sumoylation status of key proteins determines the proper progress of neurogenesis.
Gesehen am 19.06.2021